PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DENGAN MEDIA KONKRET UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA TENTANG OPERASI HITUNG PECAHAN PADA SISWA KELAS V SDN 1 KUWAYUHAN TAHUN AJARAN 2016/2017 - Nurkhotimah, Siti; Joharman, Joharman; Suripto, Suripto (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: The Use of Problem Based Learning (PBL) Model using Concrete Media in Improving Learning Outcome of Mathematics about the Operatons of Fraction for the Fifth Grade Students of SDN 1 Kuwayuhan in the Academic Year of 2016/2017. The objective of this research is to improve learning outcome of mathematics about the operations of fraction through the use of problem based learning (PBL) model using concrete media for 29 students of The Fifth Grade Students of SDN 1 Kuwayuhan. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted two meetings and also contained planning, action, observation, and reflection. Techniques of collecting data were learning outcomes test, observation, interview, and documentation. Validity of data in this research was analyzed using triangulation of sources, triangulation of technique, and content validity. The use of problem based learning (PBL) model using concrete media can improve learning outcome of mathematics about the operatons of fraction for the fifth grade students of SDN 1 Kuwayuhan in the academic year of 2016/2017. It was proven by the increase of learning outcomes in the first cycle 82,15%, in the second cycle 89,28%, and in the third cycle 96,55%.Keywords: Problem Based Learning, Concrete Media, Mathematics Abstrak: Penerapan model Problem Based Learning (PBL) dengan Media Konkret untuk Meningkatkan Hasil Belajar Matematika tentang Operasi Hitung Pecahan pada Siswa Kelas V SDN 1 Kuwayuhan Tahun Ajaran 2016/2017. Tujuan penelitian ini adalah meningkatkan hasil belajar Matematika tentang operasi hitung pecahan pada siswa kelas V SDN 1 Kuwayuhan yang berjumlah 29 siswa. Penelitian ini merupakan PTK kolaboratif yang dilaksanakan dalam tiga siklus, setiap siklus terdiri dari dua pertemuan dengan tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Teknik pengumpulan data dilakukan dengan teknik observasi, wawancara, dokumentasi, dan tes. Validitas data menggunakan triangulasi sumber, triangulasi teknik, dan validitas isi. Hasil penelitian ini menunjukkan model Problem Based Learning (PBL) dengan media konkret dapat meningkatkan hasil belajar Matematika tentang operasi hitung pecahan pada siswa kelas V SDN 1 Kuwayuhan. Pada siklus I ketuntasan belajar mencapai 82,15%, pada siklus II sebesar 89,28%, dan pada siklus III sebesar 96,55%.Kata kunci: Problem Based Learning, Media Konkret, Matematika